SHARIA MARKETING MANAGEMENT IN INCREASING FURNITURE SALES AT UD. RANDU MELATI MEUBEL PEJATEN BONDOWOSO - Abdul Barik; Siti Masrohatin; Hersa Farida Qoriani (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2026)
This study analyzes the implementation and contribution of sharia marketing management in increasing sales at UD. Randu Melati Meubel Pejaten Bondowoso. The inquiry is grounded in the premise that marketing in Islamic business is not merely an instrument for selling products, but a managerial process that creates value through honesty, responsibility, justice, transparent communication, and mutual consent. A qualitative field research design was employed. Data were collected through observation, in-depth interviews, and documentation involving the business owner, production employees, marketing personnel, and consumers of UD. Randu Melati Meubel. The data were analyzed using an interactive qualitative model consisting of data condensation, data display, conclusion drawing, and verification. The findings show that sharia marketing management is implemented through five major principles: shiddiq, amanah, tabligh, al-adl, and an-taradhin. Shiddiq appears in truthful product information, accurate specification disclosure, and the avoidance of exaggerated claims. Amanah is reflected in responsible service, fulfillment of custom orders, and willingness to handle complaints. Tabligh is realized through clear promotion using WhatsApp, Facebook, direct product displays, and word-of-mouth communication. Al-adl is reflected in fair pricing based on material cost, labor, work complexity, and reasonable profit. An-taradhin is practiced through transactions based on full information and voluntary agreement. These practices strengthen consumer trust, satisfaction, repeat purchasing, word-of-mouth recommendation, and customer loyalty. The study concludes that sharia marketing management functions both as Islamic business ethics and as a practical strategy for improving the competitiveness and sustainability of a small furniture enterprise.